In vitro evaluation of antibacterial activity of verbascoside, lemon verbena extract and caffeine in combination with gentamicin against drug-resistant Staphylococcus aureus and Escherichia coli clinical isolates - Bibi Sedigheh Fazly Bazzaz; bahman khameneh; Mohammad Reza Zahedian; Hossein Hosseinzadeh (Mashhad University of Medical Sciences, 2018)
Objective: In recent years, there has been an increasing interest in using herbal products to overcome bacterial resistance. The aim of this study was to investigate the effect of lemon verbena aqueous extract, verbascoside and caffeine in combination with gentamicin against standard and clinical isolates of Staphylococcus aureus and Escherichia coli strains. Materials and Methods: The MIC and MBC values of different antibacterial agents against bacterial strains were determined. The effect of co-administration lemon verbena extract, verbascoside, and caffeine and gentamicin was studied in vitro using a checkerboard method and calculating fraction inhibitory concentration index (FICI). Results: Herbal extract, verbascoside and caffeine alone showed no inhibitory effects on any of the bacterial strains (at doses up to 200 mg/ml). Herbal extract, verbascoside and caffeine were able to decrease the MIC of gentamicin against the standard resistant strains and two clinical isolates. Among these combinations, the co-administration of verbascoside and gentamicin was more effective and synergistic activities (FICI